Systematic Review of Microplastic Characterization Methods and Associated Toxicological Outcomes in Fish - Christian Henrich A. Garin (Tecno Scientifica Publishing, 2025)
Microplastics (MPs) have emerged as significant aquatic pollutants, yet standardized protocols for their detection and biological impact assessment remain limited. This study systematically evaluated current analytical methods used for microplastic identification and synthesized existing evidence on their reported health effects in fish. Following the PRISMA framework, a comprehensive literature search identified eight eligible studies encompassing both laboratory and field investigations. Results indicated that Raman and Fourier Transform Infrared (FTIR) spectroscopy were the most frequently employed analytical techniques. Raman spectroscopy demonstrated greater sensitivity for MPs smaller than 20 μm, whereas FTIR provided reliable identification of larger particles. Stereomicroscopy and Scanning Electron Microscopy (SEM) were also utilized, although they offered limited chemical specificity. The reviewed studies revealed species- and condition-dependent toxicological outcomes. Smaller MPs induced more pronounced oxidative stress, apoptosis, and genotoxicity, particularly in liver and muscle tissues, with perch appearing more sensitive than zebrafish. Additionally, polymer type, particle size, exposure duration, exposure route, and concentration were key determinants of toxicity. Overall, polystyrene and polypropylene were consistently linked to stronger biochemical disruptions, whereas polyethylene vinyl acetate (PEVA) and high-density polyethylene (HDPE) exhibited site-specific effects in wild-caught fish. These findings underscore the need for multi-analytical approaches and integrated biomarker assays to improve MP detection and ecological risk assessment in aquatic organisms.